Upaya Borneo Historical Community (BHC) dalam Mengenalkan Situs Bersejarah di Kota Banjarmasin - Sriwati Sriwati; Rochgiyanti Rochgiyanti; Helmi Akmal; Fathurrahman Fathurrahman; Jamaludin Jamaludin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Borneo Historical Community (BHC) is a history lover community that was founded on November 10, 2019 in Banjarmasin City. Departing from the awareness of the importance of history, this community exists to preserve and instill historical values ​​into the community. Various efforts have been made by BHC to achieve its goals, one of which is through visits to historical sites in the city of Banjarmasin. The purpose of the study was to find out how BHCs efforts were in introducing historical sites in the city of Banjarmasin. The method used in this study uses historical methods consisting of heuristics, criticism, interpretation, and historiography. The results showed that BHC made several efforts in order to introduce historical sites in the City of Banjarmasin, including: (1) conducting a survey to obtain information about historical sites in the City of Banjarmasin, (2) making a guide book containing historical sites in the city of Banjarmasin, and (3) conducting guide training for interested BHC members